2020
DOI: 10.3329/bmrcb.v46i2.49022
|View full text |Cite
|
Sign up to set email alerts
|

Association of endometrial carcinoma with obesity and diabetes mellitus

Abstract: Background: Endometrial cancer, previously referred to as carcinoma of the uterus. The incidence of endometrial cancer is raising, due to improved screening causing fewer hysterectomies in ageing population. Several studies are going on to find out the association and effects between DM and DM-related diseases, especially the cancer. Obesity and physical inactivity plays important role as modifiable determinants of insulin resistance, hyperinsulinaemia and diabetes. All these factors are also responsible for e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
0
0
Order By: Relevance
“…Diabetes mellitus is a common endocrine disorder characterized by an excessive amount of glucose circulating in the blood stream, affecting the eyes, nerves, blood vessels, skin and kidneys with long-term complications. A number of studies have been conducted on animal models (mice, rat, rabbit) to investigate anti-diabetic potential of garlic and most of these studies showed significant results [13][14][15][16][17] . Thomson et al investigated anti-diabetic effects of garlic extract at 3 incremental doses in streptozotocin-induced diabetic rats.…”
Section: Garlic As An Anti-diabetic Agentmentioning
confidence: 99%
“…Diabetes mellitus is a common endocrine disorder characterized by an excessive amount of glucose circulating in the blood stream, affecting the eyes, nerves, blood vessels, skin and kidneys with long-term complications. A number of studies have been conducted on animal models (mice, rat, rabbit) to investigate anti-diabetic potential of garlic and most of these studies showed significant results [13][14][15][16][17] . Thomson et al investigated anti-diabetic effects of garlic extract at 3 incremental doses in streptozotocin-induced diabetic rats.…”
Section: Garlic As An Anti-diabetic Agentmentioning
confidence: 99%